2015
DOI: 10.1111/jfpp.12616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan Incorporated with Cumin and Eucalyptus Essential Oils As Antimicrobial Agents on Fresh Chicken Meat

Abstract: In this study, cumin and eucalyptus essential oils were prepared and analyzed by gas chromatography-flame ionization detector. Its antibacterial effects were screened using the microdilution method for Listeria monocytogenes, Salmonella typhi, Streptococcus pyogenes and Shigella dysenteriae. The effect of the three concentrations of essential oils (0.5, 1 and 2% w/v) with 2% chitosan at 4 ± 1C temperature and storage time of up to 9 days were evaluated on the microbial quality of chicken meat. Changes in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 39 publications
0
14
0
2
Order By: Relevance
“…The MIC and MBC values were 5.625 and 11.25 mg/mL, respectively. 42 The difference antimicrobial properties of extracts and essential oils against Listeria spp may be linked to inoculation amount of bacteria, incubation time as experimental conditions, and the sources of extracts and essential oils and their chemical composition. 40 The results of this study showed, increase in the optical density values at 260 nm of L monocytogenes and L grayi treated with B persicum and E globulus essential oils over time, which can result in changes of cell membrane structure.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC and MBC values were 5.625 and 11.25 mg/mL, respectively. 42 The difference antimicrobial properties of extracts and essential oils against Listeria spp may be linked to inoculation amount of bacteria, incubation time as experimental conditions, and the sources of extracts and essential oils and their chemical composition. 40 The results of this study showed, increase in the optical density values at 260 nm of L monocytogenes and L grayi treated with B persicum and E globulus essential oils over time, which can result in changes of cell membrane structure.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high potential of essential oils and their extract as food preservatives, ingesting these at high doses can induce serious problems, and their toxicity should be considered (Sharafati Chaleshtori et al , 2013b; Bahmani et al , 2014). Therefore, several researchers have suggested the concomitant use of different food preservation systems such as modified atmosphere packaging, high hydrostatic pressure, natural antibacterial agents and biopreservation (Sharafati Chaleshtori et al , 2016; Reichling et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have already focused on natural materials such as polysaccharides [1,2], proteins [3][4][5], lipids [6], or combinations of these materials [7]. Recently, many types of gelatin-chitosan edible films [8,9] and the films incorporated with essential oils have been studied [10][11][12]. The water-soluble chitosan, fish gelatin, and D-limonene stimulated our interests to design the multifunctional films because of the following advantages.…”
Section: Introductionmentioning
confidence: 99%